PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI SEKOLAH LITTLE WORK PRESCHOOL SUNTER JAKARTA UTARA - Isnardono Isnardono; Putriani Harefa (CV. Denasya Smart Publisher, 2024)
This study aims to determine the Effect of Work Motivation on EmployeePerformance. The sampel of this study, namely employee of Little Work Preschool Sunter North Jakarta, numbered 25 people. Data collection was carried out using a questionnaire method to examine Work Motivation and Employee Performance. The validity test uses factor analysis, and the reliability test uses the Cronbach's alpha formula. The analysis prerequisite test used is the normality test. Analysis of the data used is simple regression analysis for hypotheses test. Hypothesis testing results obtained conclusions: There is a significant influence of work motivation on the performance of employee at little work Preschool in Sunter, North Jakarta. This is evidenced by the value of Sig. 0.000 <0.05 and th = 7,50.